A phylogenetic reassessment of African fossorial skinks in the subfamily Acontinae (Squamata: Scincidae): evidence for parallelism and polyphyly - Lamb, Trip; Biswas, Sayantan; Bauer, Aaron M. (Zootaxa, 2010)
The Acontinae is a well-supported clade of limbless skinks from sub-Saharan Africa for which three fossorial genera⎯Acontias, Acontophiops, and Typhlosaurus⎯have been traditionally recognized. However, recent phylogenetic analyses demonstrate conflicting support for the monophyly of Acontias and Typhlosaurus, despite limited taxon sampling for the latter genus. We re-investigate acontine evolutionary relationships, including all currently recognized species of Typhlosaurus, in phylogenetic analyses of mitochondrial (Cytb, Co1, 16s) and nuclear (Rag1) gene sequences. Our results show that Typhlosaurus is polyphyletic and represented in three distinct clades, one of which constitutes the sister lineage to other acontines. The remaining typhlosaurs form strongly-supported clades with either Acontophiops or the recently-described genus Microacontias (formerly Acontias lineatus and A. litoralis). We use this new phylogenetic framework to revise acontine taxonomy. Typhlosaurus is restricted to five species from southwestern Africa, all characterized by an attenuate body form. Acontias is expanded to include the former T. aurantiacus, T. cregoi, and T. lineatus groups as well as Acontophiops and Microacontias. Species transfer between acontine genera created two secondary homonyms; thus the affected taxa are assigned replacement names.